Internet Of Things Based Real-Time Water Quality Monitoring System For Water Storage Tank - Tan, Shin Yin (2021)
Water leaving the treatment plant should be safe and of good quality, but contamination could easily happen along the distribution pipelines. This is due to factors like rusty pipes that cause heavy metals to leach and dissolve in water, damaged or broken pipes that let soil and other contaminants or sewage enter the water. Sediments, scale and algae could also build up on water storage tanks over time. In order to keep track of water quality, this study is aimed to develop a real-time water quality monitoring system in water storage tanks that can be implemented in society, residential areas and restaurant and food service industry by utilizing Internet of Things (IoT) technology. This system employs sensors to collect water quality parameters (pH, temperature, TDS and turbidity), transmits the data wirelessly and uploads it to cloud so users can monitor remotely. The intelligent system can alert users at real-time in case of failing water quality.